Training Workshop on Numerical Weather Prediction to Improve Forecasting and Analysis of Meteorological and Earth Observations Datasets in Southern Africa Region - Amha, Yosef; Sovara, Mthetho; Bopape, Mary-Jane; Bekele, Tamrat; Demissie, Teferi Dejene; Solomon, Dawit (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
It is a well-established fact that anthropogenic climate change is amplifying the natural climate variability and extreme events (IPCC-AR6, 2018)1 . The IPCC-AR6 report confirms that climate change affected and will continue to affect African economy and society negatively although it contributes less than 4 percent of global emissions. It also indicated that Africa is warming faster than the global average where certain parts of Africa could warm up by 2.6–4.8°C by 2050. The same report highlighted that hydro-meteorological hazards due to climate change and variability (e.g., droughts, floods, windstorms, tropical cyclones, landslides and wildfire) will increase in the continent, with evidence of greater damage to the economy, ecosystem and society. The coastal systems and low-lying areas of Africa are particularly sensitive to changes in sea level, ocean temperature and ocean acidification. Consequently, extreme weather is listed as the second most severe risk on a global scale over the next 10 years in the Global Risk Report 2022 of the World Economic Forum2 . The improved early warning systems using various models including the Numerical Weather Prediction (NWP) can, therefore, assist with mitigating the severity of disasters associated with climate extreme events by improving both the accuracy and the lead-time of weather forecasts.